Francophone seniors in Ontario: A health portrait - Bouchard, Louise; Makvandi, E.; Sedigh, Golnaz; van Kemenade, Solange (Réseau de recherche appliquée sur la santé des francophones de l'Ontario, University of Ottawa, 2014)

Les aînés francophones de l’Ontario : un portrait de santé. - Bouchard, Louise; Makvandi, Ewa; Sedigh, Golnaz; van Kemenade, Solange (Réseau de recherche appliquée sur la santé des francophones de l'Ontario, Université d'Ottawa, 2014)

The health of the Francophone population aged 65 and over in Ontario. A region-by-region portrait based on the Canadian community health survey (CCHS) - Bouchard, Louise; Makvandi, Ewa; Sedigh, Golnaz; van Kemenade, Solange (Réseau de recherche appliquée sur la santé des francophones de l’Ontario & University of Ottawa, 2014)

La trajectoire des services sociaux et de santé d’aînés atteints d’une démence vivant en contexte francophone minoritaire : un engagement de multiples piliers durant une navigation complexe - Carbonneau, Corine; Drolet, Marie (Reflets, 2014)

The pathway to diagnosis of dementia for Francophones living in a minority situation - Garcia, Linda J.; McCLeary, L.ynn; Emerson, Victor; Léopoldoff, Hélène; Dalziel, William; Drummond, Neil; Cohen, Carole; Koehn, Sharon; Silvius, James (The Gerontologist, 2014)
Purpose of the Study: As the prevalence of dementia increases, the pressure to make early diagnoses also increases. Although patients must be able to identify the symptoms to access appropriate services, they may not be equally accessible to all citizens in a multicultural society. Health care professionals and patients may lack a common “first language.” This study explores the experience of francophone persons with dementia (PWD) and their caregivers during the peri-diagnostic period. Design and Methods: Individual interviews were undertaken to elicit information regarding symptoms, the role of the family and friends, and the access to formal services. Seven PWD and their caregivers who spoke French as their primary language but who lived in a primarily English-speaking region completed the interviews. Results and Implications: No single symptom seemed sufficient to alert participants that dementia might be present. Participants communicated that there was a dire need to inform the public about the signs of dementia; they spoke of the role of the family physician and the importance of having a long-standing relationship with a health professional. For some, having similar personal characteristics, such as language and culture, might accentuate the strength of the relationship and facilitate the process of diagnosis.

Access to dementia services in a minority situation: The case of Francophones in Ontario [infographic] - Garcia, Linda; Chomienne, Marie-Hélène; Cadieux, M.-A.; Farmanova, E.; McCleary, L.; Molnar, F.; Agapitos, M.; Dalziel, W.; Khoury, L.; French-Merkley, V.; Joanisse, J. (2014)

Enjeux du vieillissement chez les Africains subsahariens en milieu francophone minoritaire canadien - Mulatris, Paulin; Bahi, Boniface (Alterstice, 2014)
Les enjeux du vieillissement des populations francophones d’origine africaine subsaharienne sont très peu connus. Une analyse de données qualitatives portant sur le vécu socioculturel et les déterminants de la santé, obtenues au moyen d’entrevues semi-structurées auprès d’immigrants francophones africains subsahariens des régions urbaines d’Edmonton et Calgary, permet de constater que cette population cumule des défis culturels et économiques qui les poussent à développer un mode de vie inapproprié aux conditions d’un vieillissement en santé. La nécessité que ces Néo-Canadiens développent des habitudes de vie adaptées mène à une réflexion sur les conditions socioéconomiques auxquelles ils font face et sur l’adaptation culturelle des soins.